Peptide Presentation to T Cells: Solving the Immunogenic Puzzle: Systems Immunology Profiling of Antigen Presentation for Prediction of CD8+ T Cell Immunogenicity. (20th January 2020) - Croft, Nathan P.
Abstract: The vertebrate immune system uses an impressive arsenal of mechanisms to combat harmful cellular states such as infection. One way is via cells delivering real‐time snapshots of their protein content to the cell surface in the form of short peptides. Specialized immune cells (T cells) sample these peptides and assess whether they are foreign, warranting an action such as destruction of the infected cell. The delivery of peptides to the cell surface is termed antigen processing and presentation, and decades of research have provided unprecedented understanding of this process. However, predicting the capacity for a given peptide to be immunogenic—to elicit a T cell response—has remained both enigmatic and a long sought‐after goal. In the era of big data, a point is being approached where the steps of antigen processing and presentation can be quantified and assessed against peptide immunogenicity in order to build predictive models. This review presents new findings in this area and contemplates challenges ahead. Abstract : Antigen processing and presentation delivers peptides to the cell surface for scrutiny by T cells, alerting the immune system to detrimental states such as infection. Here, recent findings across the many steps of this process are discussed in the context of deciphering peptide immunogenicity.